Content analysis of internet marketing strategies used to promote flavored electronic cigarettes. (April 2019) - Soule, Eric K.; Sakuma, Kari-Lyn K.; Palafox, Sherilyn; Pokhrel, Pallav; Herzog, Thaddeus A.; Thompson, Noel; Fagan, Pebbles
Abstract: Introduction: Flavored e-cigarette (ECIG) use and Internet marketing have increased in the U.S. This study examined the content used to promote flavored ECIG liquids on retailer websites. Methods: Four ECIG liquid retailers from four U.S. geographic regions ( n = 16) were randomly selected. Menthol, apple, and tobacco flavored liquids were purchased in April of 2016 ( n = 144, 48 unique flavors). Staff analyzed the text and image descriptors displayed on liquid bottles and retailer websites and coded content for presence of specific flavor, taste/smell, chemesthesis (i.e., touch), America/patriotic, and product quality/potentially modified risk content. A follow-up of retailer websites was conducted in March 2018. Results: Nearly all (97.9%) ECIG liquids included a description that promoted flavor. Most descriptions including images of something other than an ECIG liquid bottle (e.g., 62% of tobacco ECIG liquid images included dried tobacco leaves, 43% of menthol ECIG liquid images included mint leaves or ice, 62% of apple ECIG liquid images included an apple). Images often promoted product sensations (e.g., cool, ice), sweet tastes of other products (e.g., chocolate, apple pie), or other appeals (e.g., America). Menthol and apple descriptions/images were more likely than tobacco descriptions/images to promote appeals related to chemesthesis (e.g., cool, warm, moist; p < .05). Most flavors were still available in 2018 and included the same flavor descriptions from 2016. Conclusions: Flavored ECIG liquid marketing often includes text descriptions and images that appeal to consumer sensations. Studies are needed to examine how access to point-of-sale Internet advertisements influences attitudes, perceptions, and purchasing of ECIG products, especially among at-risk populations such as youth. Highlights: ECIG retailers use vivid images and descriptions to promote ECIG liquids Text and images used to promote ECIG products may affect harm perceptions and appeal Research on how ECIG product marketing affects at-risk populations is needed